The Two-Way Polyphenols-Microbiota Interactions and Their Effects on Obesity and Related Metabolic Diseases - Corrêa, Telma Angelina Faraldo; Rogero, Marcelo Macedo; Hassimotto, Neuza Mariko Aymoto; Lajolo, Franco Maria (Frontiers in Nutrition, 2019)
Metabolic diseases can change the gut microbiota composition and function, and pathogenic bacteria contribute to the development of metabolic disorders. Polyphenols may act in the gut microbiota to favor the increase of beneficial bacteria and hamper the increase of pathogenic bacteria. In addition, the microbiota may act on polyphenols to increase their bioavailability. This two-way interaction between polyphenols and the gut microbiota could affect human metabolism and reduce cardiometabolic risk. Despite the possible benefits of polyphenols for human health through modulating the microbiome, studies are scarce and present several limitations. This review provides an overview of the polyphenol–microbiota interaction and its effects on metabolic disorders.